Accounting for capital: the evolution of an idea /Christopher Nobesa. - Nobesa, Christopher.
The word ‘capital’ has many meanings, within and beyond business. In accounting, it was originally a credit concept but has many uses related to assets. In economics and tax, it has exclusively asset meanings. This paper investigates the development of the concept of capital, focussing on accounting and related disciplines, especially in the UK. Even as a credit term, ‘capital’ can be as narrow as original equity or wide enough to include debt. A credit/debit confusion can be seen in Pacioli s treatise and through to recent documents by standard setters. At various dates, amounts called ‘capital’ have been shown on different sides of the balance sheet. Capital maintenance is central to the measurement of income for various purposes. It was thrown off course in 1889 by a legal case which seems to have been influenced by the double-account system, which also had echoes in economics. However, the conventional accountants’ view was re-established in 1980 because of an EU Directive. Maintenance of capital (both credit and debit forms) was much discussed in the 1970s in a period of high inflation. The concept of equity began to become clear with the separation of provisions and reserves (in the 1940s) and when liabilities were defined (from the 1960s). However, accounting practice departs from the definition and it measures liabilities in various ways, so that there is still no clear concept of equity capital. A number of policy implications are set out in the paper.